2021
DOI: 10.1177/0734242x211065231
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus speciation in sewage sludge from three municipal wastewater treatment plants in Sweden and their ashes after incineration

Abstract: Given the high efficiency in phosphorus removal at municipal wastewater treatment plants (MMWWTP), sewage sludge constitutes a promising resource for phosphorus (P) recovery. Sewage sludge is, however, a complex matrix and its direct use as fertiliser is limited by its content of metals/metalloids and organic pollutants. In order to increase its usability as a potential resource of P, there is a need for increased knowledge on phosphorus speciation in these matrices. The sludge composition is highly influenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Humans lack the ability to digest phytic acid, and a smaller fraction of the phosphorus content is therefore present in this form . However, most of the phosphorus is present as inorganic phosphorus, often aluminum- and/or iron-phosphates because iron- and aluminum-based additives are used as coagulation or precipitation agents in wastewater treatment processes. , Using chemical fractionation methods (the SMT protocol), it was shown that sewage sludge normally contain more than 70% inorganic phosphorus, out of which 60–95% was reported to be present as nonapatite phosphorus. , This includes, for example, Al- and Fe-phosphates. Solution state 31 P NMR analysis has shown similar results, and the phosphorus extracted for analysis was confirmed to be mainly orthophosphate. ,, However, some chemical fractionation studies (using the Hedley protocol) showed that more than 50% of the phosphorus is found in the acid-leachable (HCl) fraction, indicating phosphorus is associated as apatite in these sewage sludge samples. …”
Section: Phosphorus In Biomassmentioning
confidence: 99%
See 3 more Smart Citations
“…Humans lack the ability to digest phytic acid, and a smaller fraction of the phosphorus content is therefore present in this form . However, most of the phosphorus is present as inorganic phosphorus, often aluminum- and/or iron-phosphates because iron- and aluminum-based additives are used as coagulation or precipitation agents in wastewater treatment processes. , Using chemical fractionation methods (the SMT protocol), it was shown that sewage sludge normally contain more than 70% inorganic phosphorus, out of which 60–95% was reported to be present as nonapatite phosphorus. , This includes, for example, Al- and Fe-phosphates. Solution state 31 P NMR analysis has shown similar results, and the phosphorus extracted for analysis was confirmed to be mainly orthophosphate. ,, However, some chemical fractionation studies (using the Hedley protocol) showed that more than 50% of the phosphorus is found in the acid-leachable (HCl) fraction, indicating phosphorus is associated as apatite in these sewage sludge samples. …”
Section: Phosphorus In Biomassmentioning
confidence: 99%
“…The decomposition of organic phosphorus species in biomass has been studied primarily using solution state 31 P NMR ,,,,,, and chemical fractionation following the SMT protocol. , , …”
Section: Transformation Of Phosphorus In Biomass Conversionmentioning
confidence: 99%
See 2 more Smart Citations